The waiting [videorecording (DVD)] - Kelly, Bill; Noelani, Emalie; Raizor, David; Leali, Nick (Gravitas Ventures, 2022)
Eric Brady, a new hotel employee stumbling upon an open secret. One of the rooms is haunted. Eric decides it's both his and the hotel's best interest to help remove the ghost. However, when he meets the ghost, everything changed.